Multiuser Uplink MIMO Communications Assisted by Multiple Reconfigurable Intelligent Surfaces - Lv, Y.; He, Z.; Rong, Yue (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
This letter focuses on the design of multiuser uplink multiple-input multiple-output (MIMO) communications assisted by multiple reconfigurable intelligent surfaces (RISs), where we consider both linear minimal mean-squared error (MMSE) and nonlinear MMSE-decision feedback equalization (DFE) receivers. The RISs, consisting of massive low-cost passive elements, can reflect the incident signals with either continuous or discrete phase shifts. Adopting the sum mean-squared error (MSE) minimization criterion, we jointly optimize the RIS phase shifts, the linear or nonlinear receiving matrices, and the source precoding matrices in iterative manner. Simulation results show that, when the signals in direct user-access point (AP) links suffer severe attenuation, the introduction of indirect user-RIS-AP links can significantly improve the system performance.